Emergency Department Recognition of Mental Disorders and Short‐Term Risk of Repeat Self‐Harm Among Young People Enrolled in Medicaid. Issue 6 (22nd August 2017) - Bridge, Jeffrey A.; Olfson, Mark; Fontanella, Cynthia A.; Marcus, Steven C.
Abstract : Previous studies of adults have shown protective associations between clinical recognition of a mental disorder in the emergency department and short‐term risk of repeat self‐harm. Similar studies of young self‐harm patients are lacking. We conducted a retrospective longitudinal cohort analysis of national Medicaid claims data in patients aged 10–19 years with self‐harm who were discharged from emergency departments to the community ( N = 2, 703). Emergency department mental disorder recognition was not associated with a significant change in repeat self‐harm visits during the 30‐day follow‐up period. Future studies should assess whether other aspects of emergency care influence short‐term risk of repeat self‐harm.